Pack size effects on retail store inventory and storage space needs. Issue 3 (2nd August 2021) - Das, Lita; Carrel, Andre L.; Caplice, Chris
Abstract: Due to constraints on pack sizes in which products are shipped to retail stores, excess inventory can accumulate in stores. In order to optimize the allocation of store space between storage and customer-facing areas, simple expressions are required for backroom inventory levels that can be inserted into optimization models. This paper systematically investigates the effect of pack size constraints on in-store inventory and storage space needs. The context and problem definition are based on a limited service restaurant setting. An approximation for the distribution of inventory positions after replenishment is proposed, and its accuracy is compared to results obtained from simulation. Furthermore, the effect of pack size constraints on the probability of stock-outs is derived. The expressions are found to be good approximations that are usable in complex optimization models for store space allocation. Building on these results, we perform exploratory analyses and demonstrate how increasing pack sizes increases service levels but also removes revenue-generating frontroom space because by increasing backroom space requirements.